From modeling to STEM: a predictor activity of volcanic eruption. (29th August 2020) - Buber, Ayse; Unal Coban, Gul
Abstract: The purpose of this paper is to present an activity based on the integration of modeling and STEM to answer a real-life question related to volcanism which is a continuously unobservable but important phenomenon for many countries. For this purpose, firstly an activity was developed about volcanic eruptions to model the characteristics of volcanic eruptions' explosiveness. Afterwards, the participants designed a predictor of a possible eruption by using an engineering design process. The study was conducted in a public university in Turkey with twenty-four 3rd grade Pre-Service Science Teachers (PSSTs) in three weeks. In the first week, the real-life scenario was given to the PSSTs and they modeled the characteristics of volcanic eruptions' explosiveness such as viscosity, pressure, and rate of degassing. Followingly, they planned their predictors of volcanic eruptions based on what they learned in the modeling stage and started to design in the second week. In the third week, they completed their prototypes and shared their prototype development experiences with classmates. Many prototypes were presented as examples in which they used detecting the gas released from a volcano, measuring changes in the shape of the volcano, as well as monitoring earthquakes that may signal a possible eruption.